DIGITAL TRANSFORMATION IN LEGAL EDUCATION: DEVELOPMENT DIRECTIONS AND CHALLENGES - Sulistianingsih, Dewi; Adhi, Yuli Prasetyo (Prosiding Temu Ilmiah Nasional Guru, 2023)
In this research the author examines the direction and challenges of developing legal education in the era of digital transformation. The aim of this research is to describe and analyze the challenges of developing legal education in the era of digital transformation. Learning through the use of technology is a consideration in itself to achieve the required competencies. The main aim of digitizing legal education is to implement and develop digitalization in legal learning. The method used in this research is socio legal. Legally, it will review laws and regulations related to the digitalization of education. Socio-wise, it will analyze the needs and challenges faced by students in digitalizing legal education. This research uses qualitative data analysis. The results of this research show that legal education cannot be separated from digital transformation which brings legal education towards business and provides a wider reach. The challenges of developing digital transformation in legal education can be seen in two big challenges, namely internal and external. Internal challenges are human resources related to technology in learning, facilities and infrastructure related to learning, effective use of technology, changes in the role of educators, etc. External challenges are stakeholder needs for graduates, public education, the emergence of artificial intelligence in the world of education, and digital program security